National Tasawuf: The Role of Wali Songo in Building Javanese Social Order - Handoko, Rizki Nur; Priyanto, Aris; Seftio, Eko (Journal of Sufism and Psychotherapy, 2025)
Tasawwuf and nationalism including two concepts that have a deep relationship, especially in the context of developing individual and community character such as purification of the soul and national identity. character of individuals and society such as purification of the soul and national identity, unity, social care, spirituality in nation building, and facing global challenges. nation building, and facing global challenges. In this case, the Wali Songo who came to the archipelago in the 15th and 16th centuries in preaching Islam in Java used persuasive methods without violence or coercion in the process of Islamization with the aim of building an Islamic order. Islamization process with the aim of building a national order that can live in peace and work together.peacefully and work together to build Javanese civilization. Problems that will be examined in this research the basics of Sufism, the role of walisongo in building Javanese society, and the concept of tasawwuf building Javanese society, and the concept of national Sufism according to Walisongo. Research This research uses al-Ghazali's akhlaki Sufism approach which prioritizes the moral and moral aspects. moral aspects. The analysis of this research uses descriptive analysis data obtained in the form of documents obtained when documenting the required data. documents obtained when documenting the required data. In the process of preparing this scientific article using the literature review methodology, the literature review methodology is a very important step and should not be ignored. important and should not be ignored. The literature review serves as the foundation that supports the arguments and research to be carried out. Literature review methodology methodology involves collecting, analyzing, and synthesizing information from various relevant sources. relevant sources.